Six Songs, op. 75 - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Kinsky, Karoline Marie, Fürstin von, 1784-1841 (dedicatee):::Contributor:::::::::::: (Leipzig; Breitkopf and Härtel; Germany)
First edition (Leipzig) of the Six Songs, op. 75